An Investigation Into The Level Of Heavy Metals Leaching From Canal-Dreged Sediment: A Case Study Metals Leaching From Dreged Sediment. (December 2018) - Hashim, Khalid S.; Al-Saati, Nabeel H.; Hussein, Ameer H.; Al-Saati, Zainab N.
Abstract: A batch leaching test was performed to measure the leached concentrations of chromium (Cr), lead (Pb), arsenic (As), nickel (Ni), copper (Cu), cadmium (Cd), and zinc (Zn) from dredged sediment samples from the Leeds & Liverpool canal/Liverpool section. The obtained results confirmed that the leached concentrations of the studied heavy metals were less than the toxicity levels and followed the order: Zn > Cu > Ni > Pb > Cr > As > Cd. The highest concentration was of Zn (about 0.28 mg/L), followed by Cu at a concentration of 0.17 mg/L, while the lowest concentration was of Cd at 0.009 mg/L. Therefore, the dredged sediments from this canal can be safely relocated in dumping sites such as landfills, or reused such as by spreading on agricultural fields.